Management of Rice Farming Production Factors Nutrizinc Inpari 48 Farmers Group “Ngudi Makmur - Andajani, Wiwiek; Lisanty, Nina; Andarini, Marwita; Chumaidah, Siti (JURNAL AGRIBISAINS, 2024)
Public health is essential for the resilience of Indonesian society, especially for future generations, and meeting nutritional needs. Rice (paddy), a staple food for Indonesians, plays a crucial role in human health. Ensuring its safety and nutritional value requires attention to the entire production process, from seed selection, cultivation, and plant maintenance to harvest and post-harvest handling. Given the high prevalence of malnutrition and stunting, the government has initiated programs to address these issues. In 2019, the Ministry of Agriculture introduced Inpari IR Nutri Zinc, a new rice variety rich in iron and zinc, to combat these problems. The research aimed to (1) determine the feasibility of farming this variety and (2) assess the efficiency of production factor usage in Nutrizinc Inpari 48 rice farming. This quantitative study, with a descriptive approach, was conducted through a survey, intentionally selecting the "NGUDI MAKMUR" farmer group in Balerejo Village, Kauman District, Tulungagung Regency, which implements the Nutrizinc Inpari 48 rice planting program. A census method was used to sample 30 farmers. Data analysis involved (1) Feasibility Analysis: R/C Ratio and (2) Hypothesis Testing. The results concluded that Nutrizinc Inpari 48 rice farming is feasible in using production factors such as fertilizers, pesticides, and labor. This study highlights the importance of targeted agricultural interventions in improving public health through enhanced nutritional intake.